Characterization for the Convergence of Krasnoselskij Iteration for Non-Lipschitzian Operators - Ştefan M. Şoltuz; B. E. Rhoades (International Journal of Mathematics and Mathematical Sciences)
We establish the convergence of Krasnoselskij iteration for various classes of non-Lipschitzian operators.